Libya after Qaddafi: State formation or state collapse? - Wolfram Lacher (Stiftung Wissenschaft und Politik (SWP), 2011)
Under pressure from a rebellion, an international intervention, and comprehensive sanctions, Muammar al-Qaddafi's regime is on the verge of collapse. As of late March 2011, regime forces are focussed on retaining control of north-western Libya, raising the prospect of protracted civil war and partition. Qaddafi's demise is a necessary, but not sufficient, condition for Libya's renewed stabilisation. The post-Qaddafi state will essentially have to be built from scratch. However, political players will likely be more focussed on the redistribution of wealth than on building state institutions. Scenarios for the post-Qaddafi era include a new deal among former regime elites that would lead to renewed instability in the medium-term, or a more protracted, but ultimately more sustainable, state-building process. Hastening Qaddafi's fall should be the main priority of Germany and other EU member states now. External actors should also support the Interim National Council as the nucleus of a post-Qaddafi government. However, they should refrain from playing an active role in the state-building process that will follow Qaddafi's demise, as this would risk discrediting the process
Keywords: 320